Digital curation and digital literacy: Evaluating the role of curation in developing critical literacies for participation in digital culture. (September 2015) - Mihailidis, Paul
Despite the increased role of digital curation tools and platforms in the daily life of social network users, little research has focused on the competencies and dispositions that young people develop to effectively curate content online. This paper details the results of a mixed method study exploring the curation competencies of young people in digital culture. Forty-seven college students from two institutions in the north-eastern United States used the social curation platform Storify to curate essays on the topic of income inequality. Their curated stories were coded to explore for narrative development, consistency, sourcing, analysis, and content type. Regression models were used to assess clarity and balance of the curated stories, and a detailed questionnaire explored dispositions towards curation as a relevant and effective mode for engagement in digital culture. The paper argues that curation can enhance core media analysis and storytelling skills, and an understanding about the role of peer-to-peer platforms and collaborative spaces in digital culture. The results advocate the utilization of student- and creation-driven pedagogies that embrace curation as core digital and media literacy competencies for young people in daily life.